Taxonomy and phylogeny of the family Suberitidae (Porifera: Demospongiae) in California - Turner, Thomas L.; Rouse, Greg W.; Weigel, Brooke L.; Janusson, Carly; Lemay, Matthew A.; Thacker, Robert W. (Zootaxa, 2024)
This study presents a comprehensive taxonomic revision of the family Suberitidae (Porifera: Demospongiae) for California, USA. We include the three species previously known from the region, document two additional species previously known from other regions, and formally describe four new species as Pseudosuberites latke sp. nov., Suberites californiana sp. nov., Suberites kumeyaay sp. nov., and Suberites agaricus sp. nov. Multi-locus DNA sequence data is presented for seven of the nine species, and was combined with all publicly available data to produce the most comprehensive global phylogeny for the family to date. By integrating morphological and genetic data, we show that morphological characters may be sufficient for regional species identification but are likely inadequate for global classification into genera that reflect the evolutionary history of the family. We therefore propose that DNA sequencing is a critical component to support future taxonomic revisions.